2002
DOI: 10.1007/s11745-002-0945-8
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal apolipoprotein B secretion is inhibited by the flavonoid quercetin: Potential role of microsomal triglyceride transfer protein and diacylglycerol acyltransferase

Abstract: Recent studies have yielded evidence that plant flavonoids reduce hepatic lipid and apolipoprotein B (apoB) secretion. However, the possible role of flavonoids in regulating lipid and apoB secretion by the intestine has not been studied. The purpose of our study was to examine the effects of quercetin, a common dietary flavonoid, on TAG and apoB secretion in a human intestinal cell-line, CaCo-2. Differentiated postconfluent CaCo-2 cells grown on filters and pretreated with quercetin for 8 h were shown by ELISA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 33 publications
3
45
0
1
Order By: Relevance
“…The naringin-lowering effect on serum TAG levels might be related to an inhibitory effect of flavonoids on DGAT1 activity, one of the main enzymes involved in TAG synthesis in the liver (Casaschi et al, 2002;Jeon et al, 2004). In fact, these compounds were suggested for used in the clinical treatment of hypertriglyceridaemia (Casaschi et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The naringin-lowering effect on serum TAG levels might be related to an inhibitory effect of flavonoids on DGAT1 activity, one of the main enzymes involved in TAG synthesis in the liver (Casaschi et al, 2002;Jeon et al, 2004). In fact, these compounds were suggested for used in the clinical treatment of hypertriglyceridaemia (Casaschi et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the enzymatic activity of some of the proteins related to lipid metabolism (e.g. acyl-CoA : diacylglycerol acyltransferase 1 (DGAT1), acyl-CoA : cholesterol acyltransferase (ACAT), hepatic 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase) seems to be reduced by flavonoids (Casaschi et al, 2002;Jeon et al, 2002 and. However, little effort has been made to determine the effectiveness of flavonoids on the quality of ruminant products.…”
Section: Introductionmentioning
confidence: 99%
“…The flavonoid quercetin has been shown to inhibit de novo TAG synthesis [78]. Casaschi et al [78] analyzed the activity of diacylglycerol acyltransferase (DGAT), an enzyme in the final reaction of the glycerol phosphate pathway for TAG synthesis, and found reduced DGAT activity after treatment with quercetin.…”
Section: Cranberry and Dyslipidemiamentioning
confidence: 99%
“…Casaschi et al [78] analyzed the activity of diacylglycerol acyltransferase (DGAT), an enzyme in the final reaction of the glycerol phosphate pathway for TAG synthesis, and found reduced DGAT activity after treatment with quercetin. The investigators also found that quercetin inhibits microsomal TAG transfer protein (MTP) activity, an enzyme that catalyzes the transfer of lipids, such as TAG and cholesterol esters, which would inhibit intestinal apolipoprotein B secretion and total cholesterol, TG and LDL levels [78].…”
Section: Cranberry and Dyslipidemiamentioning
confidence: 99%
See 1 more Smart Citation